Mechanical Preparation of the Colon before Colorectal Surgery - Is It Still Actual? - Dragomir, Maria-Alexandra; Constantinescu, Alexandru; Andronic, Octavian (Mædica, 2024)
Mechanical bowel preparation (MBP) has long been a subject of debate in colorectal surgery. While it was historically regarded as a standard preoperative practice, recent evidence has questioned its necessity and effectiveness, especially when used in isolation. This review explores the evolving role of MBP, its combination with oral antibiotics (OA), and its impact on postoperative outcomes, such as surgical site infections (SSI) and anastomotic leakage (AL). Studies suggest that MBP combined with OA offers superior benefits compared to MBP alone, particularly in left-sided colorectal and rectal surgeries. However, the role of MBP remains contentious in right-sided resections, with conflicting evidence regarding its effectiveness. Furthermore, concerns about patient discomfort, dehydration, and electrolyte imbalances have raised doubts about its routine use. Our comprehensive analysis, based on 11 years of published research, highlights that the decision to employ MBP should be individualized, taking into account the type of surgical intervention, patient comorbidities and overall health status. While MBP+OA shows promise in reducing SSI rates, further research is needed to evaluate its broader clinical implications and to explore alternatives, including newer antibiotics, to minimize reliance on MBP.Mechanical bowel preparation (MBP) has long been a subject of debate in colorectal surgery. While it was historically regarded as a standard preoperative practice, recent evidence has questioned its necessity and effectiveness, especially when used in isolation. This review explores the evolving role of MBP, its combination with oral antibiotics (OA), and its impact on postoperative outcomes, such as surgical site infections (SSI) and anastomotic leakage (AL). Studies suggest that MBP combined with OA offers superior benefits compared to MBP alone, particularly in left-sided colorectal and rectal surgeries. However, the role of MBP remains contentious in right-sided resections, with conflicting evidence regarding its effectiveness. Furthermore, concerns about patient discomfort, dehydration, and electrolyte imbalances have raised doubts about its routine use. Our comprehensive analysis, based on 11 years of published research, highlights that the decision to employ MBP should be individualized, taking into account the type of surgical intervention, patient comorbidities and overall health status. While MBP+OA shows promise in reducing SSI rates, further research is needed to evaluate its broader clinical implications and to explore alternatives, including newer antibiotics, to minimize reliance on MBP.